Biotechnological overview - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Biotechnologies in Developing Countries: Present and Future Volume 3 Regional and Sub-Regional Co-operation, and Joint Ventures By A Sasson, Future-oriented Studies, UNESCO Publishing, 2001. 1104 pp. ISBN 92 3 103792 7 Euro 45.75